Overview of Coronary Stenosis in Menopausal Women Based on Age and Risk Factors - lalu ahmad Asmayadi (ARKAVI [Arsip Kardiovaskular Indonesia), 2019)
Overview of Coronary Stenosis in Menopausal Women Based on Age and Risk Factors Cardiovascular diseases (CVDs) take the lives of 17,9 million people every year, 31% of all global deaths. CHD occurs because of atherosclerosis or plaque that builds up in the walls of arterial blood vessels in the heart called atherosclerosis. In elderly women, menopause is one of the factors that can exacerbate coronary heart disease. CHD patients performed percutaneous coronary angiography which is a major component in cardiac catheterization, show to all branches of the coronary arteries so that they can see the degree of the plaque stenosis, location and number of narrowing. The aim of this study to describe coronary stenosis in women based on age and risk factors. The methods of this study uses descriptive research method whose data is taken in cross sectional manner from February to April 2019 at the Tangerang District General Hospital. The results of the study were 19 patients menopausal women aged 45 years and over with risk factors. The age that is most affected by coronary heart disease is 50 years old between 44-54 years. The risk factors gained in menopausal women are 68% hypertension, diabetes mellitus (DM) 16%, and hypertension with DM 16%. Then, results of many narrowing in menopausal women is 1 VD (9 patients), 2 VD (6 patients), and 3 VD (4 patients). Menopausal women are most exposed to coronary heart disease at ages 50 years old (44-54) with a risk factor of hypertension as much as 68% and most narrowing one vessel disease (1VD). Keywords: Coronary Heart Disease, Risk Factors, Menopausal, Percutaneous Coronary Angiography Gambaran Stenosis Koroner Pada Wanita Menopause Berdasarkan Usia Dan Faktor Resiko. Penyakit Kardiovaskular (PKV) merenggut nyawa 17,9 juta orang setiap tahun, 31% dari semua kematian di dunia. Penyakit Jantung Koroner terjadi karena adanya plak aterosklerosis pada dinding pembuluh darah arteri jantung. Pada wanita usia lanjut, menopause adalah salah satu faktor yang dapat memperburuk penyakit jantung koroner. Pada pasien penyakit jantung koroner dilakukan tindakan angiografi koroner perkutan yang merupakan komponen utama dalam kateterisasi jantung, bertujuan untuk memeriksa keseluruhan cabang pembuluh darah koroner sehingga dapat melihat derajat stenosis, lokasi maupun banyaknya penyempitan. Penelitian ini bertujuan untuk mengetahui gambaran stenosis koroner pada wanita berdasarkan usia dan faktor resiko. Penelitian ini menggunakan metode penelitian deskripstif yang datanya diambil secara cross sectional pada bulan Februari sampai April tahun 2019 di Rumah Sakit Umum Kabupaten Tangerang. Hasil penelitian didapatkan 19 pasien wanita menopause usia 45 tahun keatas dengan faktor resiko. Usia yang paling banyak terkena penyakit jantung koroner adalah 50 tahun (44-54). Faktor resiko yang didapat pada wanita menopause adalah hipertensi 68%, diabetes mellitus (DM) 16% dan hipertensi dengan DM 16%. Kemudian, banyaknya penyempitan pada wanita menopause adalah 1 VD (9 pasien), 2 VD (6 pasien) dan 3 VD (4 pasien). Wanita menopause paling banyak terkena penyakit jantung koroner pada usia 50 tahun (44-54) dengan faktor resiko hipertensi 68% dan paling banyak penyempitan 1 VD. Kata Kunci: Penyakit Jantung Koroner, Faktor Resiko, Menopause, Angiografi Koroner Perkutan